UJI EKSPERIMEN PENGARUH JUMLAH SUDU DAN DEBIT TERHADAP DAYA DAN EFISIENSI TURBIN AIR TIPE VORTEX - Miftakhul Na'im Kurniawan; Yuyun Estriyanto; Danar Susilo Wijayanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2024)
The electrification ratio in Indonesia is currently still 87%. This means that there are still 8.5 million residents or the equivalent of 2500 villages that have not received electricity. Indonesia has a lot of potential for renewable energy such as water energy. 7 GW capacity from renewable energy, 66% of which comes from hydropower. The manufacture of pico-hydro scale power plants can be a cheap alternative. Pico-hydro can be applied to irrigation canals so that it can produce small-scale electrical energy. One type of water turbine that can be utilized is a vortex type water turbine. The study used experimental methods. The independent variables are variations in the number of blades 2, 4, and 6 and the distance between the blades and the outlet is 1 cm. The dependent variable of the research is the power and efficiency produced by the vortex water turbine. The data analysis technique in this study used quantitative descriptive analysis techniques. The basin used is a conical basin type with the upper diameter is 40 cm, the lower/oulet diameter is 6.5 cm, and the height is 32 cm. The water discharge in this test has 7 variations, that is 1,12 l/s, 1,26 l/s, 1,54 l/s, 1,68 l/s, 1,82 l/s, 1,96 l/s, and 2,11 l/s. This test produced the highest electrical output power of 9.66 Watts, at a total of 2 blades, the discharge is 1,86 l/s. At the number of blades 6 at a discharge of 1.96 l / d is the highest efficiency value of 6.3%.